2014
DOI: 10.1177/0733464814521319
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Adult Day Services on Delay to Institutional Placement

Abstract: Delays to institutionalization were compared between elderly individuals who differed in the amounts ("dosages") of adult day services (ADS) they attended. A Kaplan-Meier survival analysis revealed higher dosages of ADS to be associated with greater delays to institutionalization. Retrospective data from financial and service utilization systems and from the Resident Assessment Instrument for Home Care (RAI-HC) were then used to fit a Cox regression model that was adjusted for potential selection biases. This … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
28
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(28 citation statements)
references
References 21 publications
0
28
0
Order By: Relevance
“…Studies in the body of literature have found positive associations between senior center attendance and self-confidence in seniors' own abilities [20], and having an increased number of acquaintances and friends [21,22]. Consistently, attending day programs at senior centers has also been found to delay institutional and nursing home placement [23,24] as well as improving wellbeing and mental wellness and reducing depression rates [19]. Ron [25] found that regular attendance to senior centers contributed to the selfesteem of older females, while Iecovich and Biderman [26] found that users of adult day care centers had significant quality of life benefits but found no evidence that users of senior centers used less health services compared with nonusers [27].…”
Section: Introductionmentioning
confidence: 96%
“…Studies in the body of literature have found positive associations between senior center attendance and self-confidence in seniors' own abilities [20], and having an increased number of acquaintances and friends [21,22]. Consistently, attending day programs at senior centers has also been found to delay institutional and nursing home placement [23,24] as well as improving wellbeing and mental wellness and reducing depression rates [19]. Ron [25] found that regular attendance to senior centers contributed to the selfesteem of older females, while Iecovich and Biderman [26] found that users of adult day care centers had significant quality of life benefits but found no evidence that users of senior centers used less health services compared with nonusers [27].…”
Section: Introductionmentioning
confidence: 96%
“…7 This, surely, has an influence on the rates of institutionalization, which are smaller when the family has support for Coexistence center for the elderly people's family Derhun FM, Scolari GAS, Castro VC, Salci MA, Baldissera VDA, Carreira L the care of the elderly. 13,14 Harmony in the family relationship is crucial for the caregiver to perform. 15 However, the caregiver's overload and the negative attitudes of the elderly provide a frailty in such a relationship, which makes care an exhausting activity and the person minimizes efforts to achieve it.…”
Section: Discussionmentioning
confidence: 99%
“…[26] Out-of-home services, such as adult day programs, provide therapeutic activities, social activities, and health monitoring for persons with dementia at an institution on a daily to weekly basis. [28] Some studies suggest that introducing HCBS earlier in the course of dementia may reduce the likelihood of NHP 28 such as the use of paid caregiver services or adult day services [29][30].…”
Section: Introductionmentioning
confidence: 99%
“…[26] Informal caregivers who make use of adult day services are more likely to utilize other HCBS due to their awareness of such supports according to some studies. [30] In light of previous research on factors influencing time to NHP in people with AD, we sought to determine if introducing home and HCBS at different stages of disease severity influenced time to NHP in a sample of persons living with AD (n = 1210); examine if disease pre-progression rate (PPR) influenced time to NHP; and explore the interaction between disease severity at first use of HCBS and PPR on time to NHP.…”
Section: Introductionmentioning
confidence: 99%